Strontium-loaded titanium surface promotes the MC3T3-E1 pre-osteoblasts growth and S. aureus adhesion - Cominotte, Mariana Aline [UNESP]; Santana, Luis Carlos Leal; de Foggi, Camila Cristina; Matos, Flavia Gomes [UNESP]; Florian, Fernanda [UNESP]; de Assis, Marcelo; Vergani, Carlos Eduardo [UNESP]; Vaz, Luis Geraldo [UNESP]; Longo, Elson; Cirelli, Joni Augusto [UNESP] (Springer Nature, 2024)
Addressing the challenges of biomedical implant failures necessitates innovative approaches within biomaterials research. This study introduces a groundbreaking methodology to enhance both osteogenic and antibacterial properties in biomedical implants focusing on strontium properties. Three titanium surfaces—machine-polished (control), alkaline-etched (AES), and strontium-loaded alkaline-etched (Sr-AES) were evaluated. The results highlight the AES and Sr-AES groups exhibit heightened surface free energy and wettability. Sr+ release peaks on days 1 and 3, tapering off later timepoints. The Sr-AES group demonstrates a trend toward increased MC3T3-E1 proliferation at days 10 and 14. Notwithstanding, the AES and Sr-AES groups presented a greater proportion of viable S. aureus compared to the control. This study unveils Sr-AES as a novel titanium surface modification, showing potential in fostering MC3T3-E1 pre-osteoblast cell growth despite lacking antibiofilm effects. These findings bear significant implications for the progression of biomedical implants, urging sustained innovation in materials design for enhanced biological compatibility. Graphical abstract: (Figure presented.).
Keywords: Biofilm; Biomaterial; Osteoblasts; Strontium; Surface chemistry; Titanium